Investigating the Impact of Missing Data Handling Methods on the Detection of Differential Item Functioning - Hüseyin Selvi; Devrim Ozdemir Alıcı (International Journal of Assessment Tools in Education)
In this study, it is aimed to investigate the impact of different missing data handling methods on the detection of Differential Item Functioning methods (Mantel Haenszel and Standardization methods based on Classical Test Theory and Likelihood Ratio Test method based on Item Response Theory). In this regard, on the data acquired from 1046 candidates who entered to Foreign National Student Exam (FNSE) held in year 2016 by Mersin University (MEU) and answered Basic Skills subtest, using different missing data handling methods, differential item functioning analyses with Mantel Haenszel, Standardization and Likelihood Ratio Test methods are performed. Basic Skills test consists of 80 multiple choice items. The items are all binary scored (1-0) items. Among the participants 523 are female and 523 are male. The findings showed that the number of items flagged as DIF has changed with the used missing data handling methods. The DIF detection methods based on Classical Test Theory are more consistent within themselves compared to DIF detection method based on Item Response Theory, whereas the used missing data handling methods differentiate the DIF detected items and this difference reaches a significant level for Mantel Haenszel method